2018
DOI: 10.1101/416016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Clinical and Molecular Epidemiology of CTX-M-9 Group Producing Enterobacteriaceae infections in children

Abstract: Background:The pandemic of extended-spectrum-beta-lactamase (ESBL)-producing-Enterobacteriaceae (Ent) is strongly linked to the dissemination of CTX-M-type-ESBL-Ent. We sought to define the epidemiology of infections in children due to an emerging resistance type, CTX-M-9-group-producing-Ent (CTX-M-9-grp-Ent). Methods:A multi-centered case-control analysis of Chicago children with CTX-M-9-grp-Ent infections was performed. Cases were defined as children possessing extended-spectrumcephalosporin-resistant (ESC-R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Most bacterial species within the Enterobacter genus are commonly found in human and animal intestines. Only a few Enterobacter species have been identified as conditional pathogens and have been described to cause extra‐intestinal and invasive infections in humans (Logan et al, ; Logan, Renschler, Sumanth, Weinstein, & Ramanan, ; Lukac, Bonomo, & Logan, ; Mogle, Beccari, Steele, Fazili, & Kufel, ). In aquaculture, the pathogenicity of Enterobacter has been reported relatively infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…Most bacterial species within the Enterobacter genus are commonly found in human and animal intestines. Only a few Enterobacter species have been identified as conditional pathogens and have been described to cause extra‐intestinal and invasive infections in humans (Logan et al, ; Logan, Renschler, Sumanth, Weinstein, & Ramanan, ; Lukac, Bonomo, & Logan, ; Mogle, Beccari, Steele, Fazili, & Kufel, ). In aquaculture, the pathogenicity of Enterobacter has been reported relatively infrequently.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the relative importance of healthcare vs. community transmission to the propagation of MDR ExPEC lineages remains poorly defined, though recent work indicates community exposures may be more important in pediatric patients. [4] The transmission dynamics of ST131-H30 (hereafter, H30) are challenging to study. Like other ExPEC lineages, H30 is known to asymptomatically colonize the gut for extended periods of time prior to-or potentially without ever-transitioning to extraintestinal infection [5].…”
Section: Introductionmentioning
confidence: 99%
“…In a multi-center study, Logan et al found that children living in South Chicago and those who were diagnosed in outpatient settings were more likely to have infections with CTX-M-9-group-producing Enterobacteriaceae. 25 Arias Ramos et al mapped ESBL-producing Enterobacteriaceae isolates from community infections and colonization events diagnosed at an urban center in Colombia. 26 Using kernel density estimations, they found hotspots of patients with community-acquired infections caused by ESBL-producing Enterobacteriaceae in various communes.…”
Section: Discussionmentioning
confidence: 99%